Biomonitoring of toxic metals in incinerator workers: A systematic review. (15th April 2017) - Mauriello, Maria Chiara; Sbordone, Carmine; Montuori, Paolo; Alfano, Rossella; Triassi, Maria; Iavicoli, Ivo; Manno, Maurizio
Highlights: Incinerators emit several potentially toxic metals. Biomonitoring is a fundamental tool for the assessment of occupational exposure. Levels of metals in incinerators workers are generally low, except for Cd and Pb. Both environmental and biological monitoring are recommended. Further studies especially focusing on other toxic metals are needed. Abstract: Exposure to chemicals released during urban waste disposal and treatment is increasingly regarded as a potential occupational health issue. Indeed, several toxic metals emitted by an incinerator, including As, Be, Cd, Cr, Pb, Mn, Hg, Ni and V, have potentially toxic properties and their exposure, therefore, may be of concern for the health of the workers involved. The levels of exposure should therefore be carefully measured. Environmental monitoring, however, may be unable, alone, to assess true exposure, due to its intrinsic limitations mainly concerning its inability to assess oral and dermal absorption. In these cases biological monitoring may represent a fundamental supplementary tool for the definition of the workers' true occupational exposure and for the prevention of the related health effects. There is, therefore, an increasing interest in developing and using, in these workers, sensitive and specific biomarkers for health risk assessment, particularly at low or even very low levels of exposure. Despite the large number of original and review articles present in the literature on the biomonitoring of workers exposed to metals, the data on subjects employed in waste treatment activities are scattered and results are sometimes inconsistent. This is the first systematic review, performed according to PRISMA methodology, of the major studies investigating the levels of different toxic metals measured in the main biological matrices (blood, urine, hair) of incinerator workers. The results show that the levels of metals measured in incinerators' workers are generally low, with some notable exceptions for Cd and Pb. These results, though, can be affected by several confounders related either to non-occupational exposure, including diet, area of residence and others, and/or by a number of methodological limitations, as we found in the reported studies. Future work should focus on an integrated approach, using ideally both biological and environmental monitoring. A particular emphasis should be given to the measurement of the different granulometric fractions of the dust containing metals, i.e. inhalable, thoracic, respirable and ultrafine fractions. Moreover, an accurate description of the work tasks and the characteristics and levels of non-occupational exposure should always be provided.